2004
DOI: 10.2746/0425164044877387
|View full text |Cite
|
Sign up to set email alerts
|

Horse‐level risk factors for fatal distal limb fracture in racing Thoroughbreds in the UK

Abstract: Summary Reasons for performing study: Fractures below the level of the radius or tibia (distal limb fractures) are the most common cause of equine fatality on UK racecourses; however, little is known about their epidemiology or aetiology. Identification of risk factors could enable intervention strategies to be designed to reduce the number of fatalities. Objectives: To identify horse‐level risk factors for fatal distal limb fracture in Thoroughbreds on UK racecourses. Methods: A case‐control study design w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
101
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(124 citation statements)
references
References 21 publications
17
101
3
Order By: Relevance
“…In our study a higher risk of injury was found for older horses. The age of the horse has been shown to be associated with the risk of injury in a number of studies (Estberg et al, 1996b;Bailey et al, 1997;Cohen et al, 1997;Cohen et al, 2000;Parkin et al, 2004a;Perkins et al, 2005). This consistent association might be because older horses continue to accrue microdamage and injury risk.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In our study a higher risk of injury was found for older horses. The age of the horse has been shown to be associated with the risk of injury in a number of studies (Estberg et al, 1996b;Bailey et al, 1997;Cohen et al, 1997;Cohen et al, 2000;Parkin et al, 2004a;Perkins et al, 2005). This consistent association might be because older horses continue to accrue microdamage and injury risk.…”
Section: Discussionmentioning
confidence: 96%
“…The risk of fracture was also higher for horses that did no gallop work during training (Parkin et al, 2005) but horses that accumulated an excess timed work distance within a 2 month period prior a race were at higher risk as well (Estberg et al, 1996a). Exercise history (Estberg et al, 1996a,b;Estberg et al, 1998a,b) (Cohen et al, 2000) (Hernandez et al, 2005;Parkin et al, 2005) and specifically the distance galloped in training (Estberg et al, 1995;Estberg et al, 1996a,b;Estberg et al, 1998a,b;Cohen et al, 2000;Parkin et al, 2004a) have also been associated with injuries.…”
Section: Introductionmentioning
confidence: 99%
“…There are various factors influencing the length of racing career of horses. Although musculoskeletal injuries are considered to be the major reason for career ending (2,3,26,38), studies showed that many other risk factors such as age at first start (37), gender (14), exercise intensity (14,24), race distance (25), track condition (1) are also related with career ending.…”
Section: Introductionmentioning
confidence: 99%
“…Parkin, Clegg et al (2004c) reported that horses which did zero fast work were 3.13 times more likely to have catastrophic fracture of the distal limb compared to horses which galloped two to 7 furlongs per week (95% CI 1.10 -8.91, P = 0.03). Short distances of gallop work were also shown to be protective against fracture and further supported by two other United Kingdom studies (Verheyen, Price et al 2006a, Verheyen, Newton et al 2006b).…”
Section: Exercise Intensitymentioning
confidence: 99%
“…Two retrospective case control studies showed the risk of distal limb catastrophic fracture (OR 3.1, 95% CI 1.1 -8.9, P = 0.02, Parkin, Clegg et al 2004c) and in particular with lateral condylar fractures was greatest for horses which accumulated zero furlongs per week (OR 5.26, 95% CI 1.86 -14.90, P = 0.002, Parkin, Clegg et al 2004b). In contrast to the Kentucky study, the United Kingdom studies also reported the age at first racing start which takes into account when racehorses were most adapted to start a race (Parkin, Clegg et al 2004b, Parkin, Clegg et al 2004c. Horses which started their racing careers at three or four were at greatest risk of catastrophic lateral condylar fracture when compared with two year olds (OR 2.71, 95% CI 1.36 -5.42, P < 0.005).…”
Section: Exercise Intensitymentioning
confidence: 99%